2012
DOI: 10.1073/pnas.1119496109
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal representations of distance in human auditory cortex

Abstract: Neuronal mechanisms of auditory distance perception are poorly understood, largely because contributions of intensity and distance processing are difficult to differentiate. Typically, the received intensity increases when sound sources approach us. However, we can also distinguish between soft-but-nearby and loud-but-distant sounds, indicating that distance processing can also be based on intensity-independent cues. Here, we combined behavioral experiments, fMRI measurements, and computational analyses to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
47
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 60 publications
9
47
3
Order By: Relevance
“…Previous studies addressed this issue by comparing sounds of different spectral structure: complex tones elicited stronger behavioral looming bias (2, 11) and larger neural differences (14-16) than did noise with equal intensity increase, indicating that intensity changes did not directly cause looming bias. However, studies with a different spatial task (17) or species (10) found the opposite effect (i.e., stronger looming bias for noise than tonal sounds), calling into question these results.An early fMRI study that contrasted static sounds with sounds increasing or decreasing in intensity found activity in the right planum temporale (4), which is associated with processing of auditory motion in any spatial direction (18,19), consistent with the idea that sound intensity changes can be perceived as motion in distance. The contrast between sounds increasing vs. decreasing in intensity, however, revealed a different network, including superior temporal sulcus and amygdala, which may reflect a warning process for approaching objects (4,9,20).…”
mentioning
confidence: 72%
See 3 more Smart Citations
“…Previous studies addressed this issue by comparing sounds of different spectral structure: complex tones elicited stronger behavioral looming bias (2, 11) and larger neural differences (14-16) than did noise with equal intensity increase, indicating that intensity changes did not directly cause looming bias. However, studies with a different spatial task (17) or species (10) found the opposite effect (i.e., stronger looming bias for noise than tonal sounds), calling into question these results.An early fMRI study that contrasted static sounds with sounds increasing or decreasing in intensity found activity in the right planum temporale (4), which is associated with processing of auditory motion in any spatial direction (18,19), consistent with the idea that sound intensity changes can be perceived as motion in distance. The contrast between sounds increasing vs. decreasing in intensity, however, revealed a different network, including superior temporal sulcus and amygdala, which may reflect a warning process for approaching objects (4,9,20).…”
mentioning
confidence: 72%
“…An early fMRI study that contrasted static sounds with sounds increasing or decreasing in intensity found activity in the right planum temporale (4), which is associated with processing of auditory motion in any spatial direction (18,19), consistent with the idea that sound intensity changes can be perceived as motion in distance. The contrast between sounds increasing vs. decreasing in intensity, however, revealed a different network, including superior temporal sulcus and amygdala, which may reflect a warning process for approaching objects (4,9,20).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…In humans, the putative posterior auditory “ where ” pathway, encompassing the planum temporale (PT) and posterior superior temporal gyrus (STG), is strongly activated by horizontal sound direction changes (Ahveninen et al, 2006; Brunetti et al, 2005; Deouell et al, 2007; Tata et al, 2005), movement (Baumgart et al, 1999; Formisano et al, 2003; Krumbholz et al, 2005; Warren et al, 2002), intensity-independent distance cues (Kopco et al, 2012), and under conditions where separation of multiple sound sources is required (Zündorf et al, 2013). However, it is still unclear how the human AC encodes the acoustic space: Is there an orderly topographic organization of neurons representing different spatial origins of sounds, or are sound locations, even at the level of non-primary cortices, computed by neurons that are broadly tuned to more basic cues such as ITD and ILD, using a “two-channel” rate code (McAlpine, 2005; Middlebrooks et al, 1994; Middlebrooks et al, 1998; Stecker et al, 2003; Werner-Reiss et al, 2008)?…”
Section: Non-invasive Studies Of Spatial Processing In Human Auditmentioning
confidence: 99%